Conceptual approach to lateral salinity gradients around roots of salt-sensitive and salt-tolerant crops under irrigation conditions - Schleiff, Uwe (Ecological Questions, 2011)
Under controlled crop irrigation with brackish water, a vertical soil salinity gradient develops in the rooted soil layer. Furthermore, in periods of soil water depletion, due to ion exclusion by roots, a transpiration-driven, lateral build-up of a salinity gradient between the soil fraction adjacent to roots and distant, occurs. Root morphological traits determine the volume of the soil fraction, in which salt accumulation occurs (rhizospheric soil volume). The increase of soil salinity near roots is greater, when plant roots form a small rhizospheric soil volume (e.g. leek). When roots form a larger rhizospheric soil volume, salts are distributed throughout a larger soil volume, which improves conditions for root water uptake and crop salt tolerance (e.g. rape).